THE ANTECEDENTS OF CUSTOMER SATISFACTION AND ITS IMPACT ON CUSTOMER LOYALTY : (The study of Merry’s Cake Lampung) - Adi Gunawan; Andala Rama Putra Barusman; Selfia Alke Mega; Wenny Permata Sari (Journal of Management, Business and Social Sciences, 2023)
This study aims to determine the effect of customer preferences on product quality, service quality, product image on customer satisfaction and customer loyalty in the Merry's Lampung pastry business. The research method used in this research is a purposive random sampling method with 200 customers as respondents and uses the SEM (Structural Equation Modeling) analysis method. the results of this study note that product quality has a positive and significant influence on customer satisfaction and on customer loyalty, service quality has a positive and significant influence on customer satisfaction and on customer loyalty, product image has a positive and significant influence on customer satisfaction and loyalty and then customer satisfaction as an intervening variable has a positive and significant influence on customer loyalty. The recommendation obtained in this study are Merry's Lampung pastry business managers need to innovate such as making more attractive cake shapes, more unique packaging, ease of payment, adding premium products and improving facilities to increase customer satisfaction and customer loyalty.